Study on the sleep–wake circadian rhythm and phenotypic characteristics in the acute phase of hemorrhagic stroke - Yuan, Xiaodong; Fu, Yongshan; Ou, Ya; Xue, Jing; Yang, Na; Liu, Hongrui; Wang, Tiantian; Wang, Jing; Yan, Cuiping; Zhang, Pingshu (Frontiers in Neuroscience, 2025)
ObjectiveTo investigate the sleep–wake circadian rhythm and phenotypic characteristics in patients with acute intracerebral hemorrhage (ICH), and to explore the relationship and potential mechanisms between sleep–wake phenotypes and circadian rhythm disruption.MethodsA retrospective analysis was conducted on 100 patients with acute ICH admitted to Kailuan General Hospital between January 2020 and December 2024, along with 67 age- and sex-matched hospitalized controls. Sleep parameters during the daytime (06:00–18:00) and nighttime (18:00–06:00) were collected using a mattress-based sleep monitoring system. Circadian rhythm indices—including interdaily stability (IS), intradaily variability (IV), and relative amplitude (RA)—as well as sleep phenotypic features were evaluated.ResultsCompared with the control group, patients with ICH exhibited significantly disrupted circadian rhythms, characterized by reductions in IS, IV, and RA (all p < 0.05). Significant alterations in sleep–wake states were observed in both daytime and nighttime periods among ICH patients. These included prolonged/increased durations and proportions of light sleep, deep sleep, NREM sleep, REM sleep, and sleep efficiency, along with shortened/decreased sleep latency, REM latency, and proportion of NREM sleep (all p < 0.05). Phenotypic analysis revealed a significantly higher prevalence of excessive daytime sleep, increased total sleep across 24 h, and reversed sleep–wake cycles in the ICH group (all p < 0.05). Regression analysis indicated that reduced IS was significantly associated with reversed sleep–wake cycles (OR = −5.831; 95% CI,: −12.577 −1.350).ConclusionAcute hemorrhagic stroke is associated with excessive sleepiness, disrupted sleep architecture, and weakened circadian rhythms. These disturbances may impair recovery and long-term outcomes, underscoring the need for rhythm-based biomarkers and individualized interventions.